SENSORY INTEGRATION: DIFFERENCE IN PATTERNS CORTICAL WAVE POST-TRAINING IN COMPLEX PSYCHOMOTOR TASK (Fiep Bulletin - online, 2011)
Referenced to sensory integration phenomenon it was investigated a possible relationship between sensory stimulation load and learning rateio of a complex psychomotor task. Sample of two boys, twins, 7 years old. After the task baseline and standard electroencephalographic alpha measures, one of the twins practiced a low stimuli load circuit, and the other a high load one, for 30 days. Statistics of the data pre and post-circuits associated a better performance to the high stimuli load practitioner (P
Keywords: sensory integration; Psychomotor learning; EEG